Model test study on the stability of cobble strata during shield under-crossing. (April 2021) - Lin, Qingtao; Lu, Dechun; Lei, Chunming; Tian, Yu; Gong, Qiuming; Du, Xiuli
Highlights: A test platform for the earth pressure balance shield is designed and manufactured. A test of the shield under-crossing existing tunnels in cobble strata is conducted. Disturbance mechanism of the cobble strata around the existing tunnel is revealed. Deformation feature of the existing horseshoe and rectangular tunnels is obtained. Abstract: A test platform of the earth pressure balance shield is designed and manufactured. Taking a field project as the background, the test model with single cobble strata and two existing tunnels is planned, and the test of shield under-crossing the existing tunnels in the cobble strata is conducted. The surface settlement, the normal earth pressure acting on the existing tunnel, and the circumferential strain of the existing tunnels are measured. During the shield advancing process, two collapse pits are caused on the ground surface directly above the right side walls of the horseshoe tunnel and rectangular tunnel, respectively. Based on the measured surface settlements and the earth pressure on the existing tunnels, collapse mechanism of the cobble soil around the existing tunnel is revealed. Meanwhile, deformation feature of the existing horseshoe and the rectangular tunnels is obtained according to the measured circumferential strain.